Concomitant trocar-guided transvaginal mesh surgery with a midurethral sling in treating advanced pelvic organ prolapse associated with stress or occult stress urinary incontinence - Chia-Jen Wu; Fei-Chi Chuang; Li-Ching Chu; Fu-Tsai Kung; Kuan-Hui Huang; Ming-Ping Wu (Elsevier, 2013)
Objective: The purpose of this study was to evaluate the efficacy and feasibility of concomitant trocar-guided transvaginal mesh (TVM) surgery with a midurethral sling (MUS) for treating women with advanced pelvic organ prolapse (POP) and stress urinary incontinence (SUI) or occult SUI (OSUI). Materials and methods: Eighty-nine women with advanced POP and SUI or OSUI were retrospectively enrolled. The Total Prolift and Tension-free Vaginal Tape-Obturator Systems were used for trocar-guided TVM surgery and MUS. Patients received regular follow-up at 1 week, and 1 month, 3 months, 6 months, and 12 months postoperatively, and then annually thereafter. The endpoints were the success rate for POP, and perioperative and postoperative complications. Functional outcomes were the presence of voiding difficulty, persistent or de novo overactive bladder symptoms, postoperative SUI, and paresthesia. Results: The median follow-up period was 35 months (range, 12-50 months). Within the follow-up period, 84 patients (94.4%) were objectively cured, five patients (5.6%) had vaginal apical mesh exposure, 29 individuals (32.6%) had persistent or de novo overactive bladder symptoms, six individuals (22.5%) had de novo SUI (two were found by urodynamics), and nine individuals (10.1%) had voiding difficulties (two were found by urodynamics). In addition, the vaginal hysterectomy group had greater blood loss, longer operation times, and a higher mesh erosion rate compared to the uterine suspension group. Conclusion: Concomitant trocar-guided TVM surgery and MUS with the use of total Prolift and Tension-free Vaginal Tape-Obturator offer good efficacy in treating women with advanced POP and SUI or OSUI. The vaginal hysterectomy group had more perioperative complications.